5
$\begingroup$

I have a problem with this limit question. $$\lim_{x \to \infty} \frac{x^3-4x}{7-2x^3}$$

How can the answer become $-\frac12$?

$\endgroup$
2
  • 3
    $\begingroup$ divide numerator and denominator by $x^3$ and note that as $x \to \infty$, $1/x \to 0$ $\endgroup$
    – AgentS
    Sep 9, 2014 at 13:49
  • $\begingroup$ If this doesn't make sense to you you should probably think about which terms "dominate" in the numerator and denominator as x gets big. The cubed terms dominate as x gets big, and then it's just the ratio of the coefficients. $\endgroup$
    – user420667
    Sep 9, 2014 at 19:36

4 Answers 4

16
$\begingroup$

Factor the term with the highest power (here, $x^{3}$) :

$$ \begin{align*} \lim \limits_{x \to +\infty} \frac{x^{3}-4x}{7-2x^{3}} &= {} \lim \limits_{x \to + \infty} \frac{\require{cancel} \cancel{\color{blue}{x^{3}}} \big( 1 - \frac{4}{x^{2}} \big)}{\require{cancel} \cancel{\color{blue}{x^{3}}}\big( \frac{7}{x^{3}} - 2 \big)} \\[2mm] &= \lim \limits_{x \to +\infty} \frac{1 - \frac{4}{x^2}}{\frac{7}{x^3}-2} \\[2mm] &= \frac{1}{-2} \\[2mm] &= -\frac{1}{2} \end{align*} $$

$\endgroup$
10
$\begingroup$

$$\frac{x^3-4x}{7-2x^3}=\frac{1-\frac{4}{x^2}}{\frac{7}{x^3}-2}$$

when $x\ne 0$. Now take the limit.

$\endgroup$
0
4
$\begingroup$

Use L'hopital's rule, you have to derivate three times: $$\lim_{x\to \infty}(x^3-4x)/(7-2x^3)=\lim_{x\to \infty}(3x^2-4)/(-6x^2)=\lim_{x\to \infty}(6x)/(-12x)=\lim_{x\to \infty}(6)/(-12)=-1/2$$

$\endgroup$
2
  • 8
    $\begingroup$ This is the proverbial sledgehammer to crack a nut... $\endgroup$ Sep 9, 2014 at 16:50
  • 1
    $\begingroup$ For this solution to be correct, you need to show that the original expression is an indeterminate form $\infty/\infty$, which is not completely obvious from the expression as written. $\endgroup$ Sep 9, 2014 at 18:43
1
$\begingroup$

Here are the steps $$ \lim_{x\to\infty} \frac{x^3-4x}{7-2x^3}= \lim_{x\to\infty} \frac{\frac{x^3}{x^3}-\frac{4x}{x^3}}{\frac{7}{x^3}-\frac{2x^3}{x^3}}= \lim_{x\to\infty} \frac{1-\frac{4}{x^2}}{\frac{7}{x^3}-2} =\frac{1-0}{0-2}=-\frac{1}{2} $$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.